Norma e transgressão - Carmen Soares (Documentos, 2008)
Identity is constructed through the interaction between the 'I' and the numerous 'others' that constitute its world. From this plurivocal dialogue results a diversity of ways of acting and thinking, responsible not only for the creation of norms but also for passing beyond the transmitted code, that is, for transgression. It is the constant updating of this dynamic correlation between norm and transgression that gives rise to progress (moving forwards) of the 'I', both individual and collective. In it lies the very nature of creative activity, the fascination for discovery, the impulse and need for revolution.